Zbrodnia inkorporowana. O konwencji „paranoicznego gotyku” w Zbrodni z premedytacją Witolda Gombrowicza - Warkocki, Błażej (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The article presents the analysis and interpretation (in the form of a close reading) of Witold Gombrowicz’s short story The Premeditated Crime from his debut collection Memoirs from a Time of Immaturity , 1933 (later published under the title Bakakaj or Bacacay in the English translation). The main theoretical framework is the concept of „paranoid Gothic” by Eve Kosofsky Sedgwick, which is based on the reinterpretation of Sigmund Freud’s classic essay Psychoanalytical comments on autobiographically described paranoia . From that perspective Gombrowicz’s narrative is interpreted as a paranoid homosexual narrative, and paranoia itself as a form of love.